Satellite Farming An Information and Technology Based Agriculture - Ahmad, Latief (Springer International Publishing, 2018)
This book focuses on the recent advances in precision agriculture and satellite farming, detailing applications for sensing, data handling, modeling, and control. In addition, the book reviews its history - establishing the background on the various processes and applications - describes the current status, and offers insight into the future technology of satellite farming in India. Introducing processes and applications based on a global scale, the book reveals how precision agriculture can be used in large-scale agriculture, community agriculture, and diversified farming. It includes site-specific information from a variety of information sources for planning, planting, growing, and harvesting agricultural crops. It also presents a new concept based on the control system theory that can be used to formulate systematic methods for more effective precision crop production. Precision agriculture when properly integrated into the crop production process, can greatly improve overall production and sustainability. .